Is complete umbilical cord scanning possible at the second‐trimester ultrasound scan?. Issue 4 (1st October 2014) - Ugurlucan, Funda Gungor; Yuksel, Atil
ABSTRACT Purpose To evaluate the feasibility of umbilical cord scanning during the second‐trimester sonographic examination, we looked at the method of scanning, the findings, and the time spent. Methods Five hundred forty‐nine singleton pregnancies were evaluated at 18–23 weeks' menstrual age with two‐dimensional sonography (US). Color Doppler US was used when needed. The umbilical cord was traced from the fetal insertion site to the placental insertion site. Fetal and placental sites of insertion; number of vessels; presence of knots, cysts, tumors, nuchal cords, or placental anomalies; time spent for scanning; and the use of color Doppler US were noted. Results The mean maternal age was 33.1 ± 4.1 years, and the mean menstrual age of the fetuses during scanning was 20.4 ± 2.4 weeks. The mean time spent for umbilical cord scanning was 41.5 ± 46.7 seconds. In one case (0.2%), the umbilical cord could not be scanned completely. Color Doppler US was needed in 125 (22.8%) of the scans. Scan results were positive in 153 (27.9%) cases. We observed six cases (1.1%) of a single umbilical artery, two (0.4%) umbilical cord knots, one (0.2%) umbilical cord hernia, and 104 (18.9%) nuchal cords. We also documented 27 (5.0%) marginal insertions, four placenta previa totalis (0.7%), four placenta previa marginalis (0.7%), and eight velamentous insertions (1.5%). Conclusions Umbilical cord US scanning is feasible during the second trimester of pregnancy, and complete scanning can be performed in the majority of the cases. Color Doppler analysis may aid scanning when needed. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:249–253, 2015